2005
DOI: 10.1111/j.1439-0396.2005.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium phytate supplementation on fat digestion and cholesterol metabolism in female rats

Abstract: The effects of sodium phytate supplementation on fat digestion and cholesterol metabolism were investigated in female rats. On the basis of an in vitro experiment showing that phytate raised the solubility of bile acids, it was predicted that phytate feeding would depress faecal bile acid excretion, raise apparent fat digestibility and elevate serum cholesterol concentrations. The experimental diets with or without sodium phytate were either cholesterol-free or cholesterol-rich and had a normal calcium concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…The observed decrease in hepatic lipogenic enzyme activities in this study may also be explained by Yuangklang et al [30] report that calcium-phytate complex does not bind bile acids which suggests maintenance of bile acids pool and nonutilization of cholesterol for bile acid synthesis with subsequent elevation in serum cholesterol.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The observed decrease in hepatic lipogenic enzyme activities in this study may also be explained by Yuangklang et al [30] report that calcium-phytate complex does not bind bile acids which suggests maintenance of bile acids pool and nonutilization of cholesterol for bile acid synthesis with subsequent elevation in serum cholesterol.…”
Section: Resultssupporting
confidence: 77%
“…The elevated cholesterol noted in our study may be attributed to the use of calcium-magnesium phytate rather than sodium phytate used in other studies. In an in vitro study carried out by Yuangklang et al [30], calcium phytate complex was shown not to bind bile acids. They also suggested that this may reduce fecal bile excretion and increase serum cholesterol in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, the apparent absorption of total lipid and cholesterol was also reduced, whereas fecal cholesterol and lipid contents were increased by the dietary phytic acid. Yuangklang et al (2005) also reported increased excretion of bile acids in feces and reduced concentration of cholesterol in the liver of rats fed a cholesterol rich diet by 28 and 22%, respectively, due to an increase in dietary phytic acid concentration from 0 to 0.33%. However, the increased fecal excretion of bile acids did not translate to reduced fat digestibility and serum cholesterol concentration and the reason for this is not clear.…”
Section: Effect Of Phytic Acid On Energy Digestibilitymentioning
confidence: 88%
“…Moreover, in vivo trials have shown that the trypsin activity does not necessarily conform with protein digestibility (Sajjadi and Carter, 2004). Likewise, Yuangklang et al (2005) concluded from a study where sodium phytate had an effect on bile acids in vitro, that there was no relationship with in vivo lipid digestibility in rats. The use of different protein sources in different studies may also explain contradictory effects of IP6 on utilization of main nutrients (Kies et al, 2006) The solubility profile of protein from different sources such as soya, canola, sunflower and maize vary with pH levels, and the presence of IP6 has a significant effect on the solubility of protein.…”
Section: Discussionmentioning
confidence: 99%